Evaluasi Contoh Uji Dari DKI Jakarta Tahun 1986-1987 Di Balai Pengembangan Pupuk Dan Petrokimia - Endang Rachmayani (Jurnal Kimia dan Kemasan, 1987)
"The role of quality control in Development Division for fertilizer and petro chemical (Balai Pengembangan Pupuk dan Petrokimia) include raw material and product testing. In 1986 - 1987, they were three hundred eighty four commodities had been tested, sixty three were not certified with mayority of salt, resin alkyd modifikasi minyak nabati and hewani, carbon active and water commodities. It is very important to improve quality of products, so they will accomplish their standard.